Diffuse lesion and necrosis tied to poorer prognosis of interdigitating dendritic cell sarcoma: cases report and a pooled analysis - Feng Shi (Nature Portfolio, 2017)
Abstract Interdigitating dendritic cell sarcoma is a neoplastic proliferation of interdigitating dendritic cells and no therapeutic consensus exists. This study aimed to investigate the prognostic impacts of tumor lesion, cellular atypia, mitosis and necrosis on the interdigitating dendritic cell sarcoma. Case reports and pooled analyses were designed to explore the relationships. One case was a 40-years old man with localized lesion, moderate to notable cellular atypia, 30 mitoses per 10 high-power fields and no necrosis and the progression-free survival was longer than 20 months. The other case was a 62-years old woman with diffuse lesion, notable cellular atypia, less than one mitosis per 10 high-power fields and diffuse necrosis and the progression-free survival was shorter than 1 month. Cellular atypia and mitosis had not any relationship with survival. Compared with localized lesion, diffuse lesion presented a 2.92-fold risk of progression (HR = 2.92, 95% CI 1.01, 8.51) and an 8.79-fold risk of death (HR = 8.79, 95% CI 1.86, 41.64). Diffuse necrosis presented a 4.39-fold higher progression risk (HR = 5.39, 95% CI 1.78, 16.29) and a 5.37-fold higher death risk (HR = 6.37, 95% CI 1.46, 27.86) than focal or no necrosis. Diffuse lesion and diffuse necrosis were indicators of poorer prognosis and the clinical application should be warranted in further studies.